Analysis Of Pipeline Erosion By CFD Simulation Under The Effect Of Sand Particles of Water and Ethylene Glycol - Sandeep Gaur (AG Volumes, 2021)
Sand productions include a variety of main essential difficulties for gas and oil productions, as sand managements are increasingly becoming crucial to manage wells with high rates of sand accumulation. Approximately 70 percent of the world’s gas and oil reserves are found in sand deposits. Sand erosion over a pipe bend is studied in this research, which examines and analyses many aspects to determine the sand’s severity and quantity of erosion. For this work, computational fluid dynamics (CFD) was employed to analyse the fluid flow phenomenon. The sand particle sizes of 160m and 370m will be compared in this experiment to see how different percentages of water and EG may affect the results. The three primary impacts that will be investigated further are erosive rate, skin friction coefficient, and swirl velocity. Through the investigation, it can be concluded that the character of the material and the flow velocity are the most important elements influencing the rate of sand erosion in pipelines.